The Possible Responses of Polar Ozone to Solar Proton Events in March 2012 by FengYun‐3 Satellite Observations. Issue 12 (2nd December 2019) - Huang, Cong; Huang, Fu‐Xiang; Zhang, Xiao‐Xin; Lv, Jing‐Tian; Cao, Dong‐Jie; Liu, Dan‐Dan
Abstract: In this work, we use observations by the Solar Backscatter Ultraviolet Sounder and Space Environment Monitor on FengYun‐3 to analyze the polar ozone depletion during the solar proton events (SPEs), which occurred in early March 2012. The ozone distributions changed evidently with the increasing energetic proton flux (the particle energy is over 100 MeV) at the approximate altitude of 30 km. From the ozone profile relative changes, the short‐term impacts of SPEs can be distinguished from the long‐term effects of ozone season variations after the SPEs take place and cause about 4–17% of the short‐term polar ozone decreases at the different levels in the upper stratosphere of both hemispheres. In the upper stratosphere, the SPE‐related polar ozone depletion is more significant and continuous in the Northern Hemisphere but shows the short‐term effects in the Southern Hemisphere during the March SPEs. The ozone depletion responses to the first SPE on 7 March are more pronounced in this altitude region than the second one on 13 March in both hemispheres due to the "harder" particle energy spectrum. Key Points: Short‐term polar ozone depletion is significant in the upper stratosphere of both hemispheres due to solar proton events in March 2012 Solar‐proton‐event‐induced polar ozone changes are more pronounced in the Northern Hemisphere The polar ozone content decreases about 4–17% at the different levels in the upper stratosphere during the March 2012 solar proton events